Kebijakan dan kepemimpinan pendidikan islam di indonesia pada masa orde reformasi - Sahbana, M. Dwi Rahman; Dinata, Syaiful (LP2M STAI Darul Kamal NW Kembang Kerang NTB, 2022)
The purpose of this study is to analyze the policies and leadership of Islamic education in Indonesia during the Reformation Order. Research in this paper uses literature study, namely research whose subject is in the form of literature. The results of this study say that the government at that time had different policies in national education and religious education, including Islam. In this study, there were five presidential terms, namely those of Habibie, Abdurrahman Wahid, Megawati Soekarnoputri, SBY and Jokowi. With different leadership and policies by each president, the author analyzes national education policies and Islamic education during his reign. The results of the analysis are that first Habibie made the campus free from NKK intervention and review and changed PTN status to BHMN, Second Abdurrahman Wahid issued regional financial balancing laws, Third Megawati Soekarnoputri raised the degree of religious subjects or courses which became number one in education, equalizing between education under the auspices of the Ministry of Education and Culture and KEMENAG, both in terms of institutions, teachers and lecturers and students who are involved in it, Fourth SBY emphasized the administration of institutions and the prosperity of teachers, Fifth Jokowi the most famous breakthrough was the implementation of online learning due to the impact of Covid-19